2023
DOI: 10.3390/biomedicines11051308
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Oxidative Stress during the Recovery Phase in Critical COVID-19 Patients in a Rehabilitation Facility: Potential Utility of the PAOT® Technology for Assessing Total Anti-Oxidative Capacity

Abstract: Background: Oxidative stress (OS) could cause various COVID-19 complications. Recently, we have developed the Pouvoir AntiOxydant Total (PAOT®) technology for reflecting the total antioxidant capacity (TAC) of biological samples. We aimed to investigate systemic oxidative stress status (OSS) and to evaluate the utility of PAOT® for assessing TAC during the recovery phase in critical COVID-19 patients in a rehabilitation facility. Materials and Methods: In a total of 12 critical COVID-19 patients in rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
(108 reference statements)
1
0
0
Order By: Relevance
“…Pincemail et al . [ 22 ] in a recent study reported that oxidative stress was found to be higher during the recovery phase of critical COVID-19 patients and found that salivary TAC levels were decreased, which is in accordance with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Pincemail et al . [ 22 ] in a recent study reported that oxidative stress was found to be higher during the recovery phase of critical COVID-19 patients and found that salivary TAC levels were decreased, which is in accordance with the present study.…”
Section: Discussionsupporting
confidence: 93%